2017
DOI: 10.5371/hp.2017.29.4.228
|View full text |Cite
|
Sign up to set email alerts
|

Primary Total Hip Arthroplasty Using Summit® Stems in Korean: Minimum Four-year Follow-up

Abstract: PurposeThe aim of this study was to assess the mid-term results of primary cementless total hip arthroplasty (THA) using Summit® stems.Materials and MethodsOne hundred twenty-eight arthroplasties in 121 patients who were performed THA from December 2004 to March 2013, were reviewed retrospectively a minimum of 4 years follow-up (mean age, 60.3 years; mean postoperative follow up period, 86.3 months). For a clinical evaluation, the Harris hip score (HHS) was used to assess outcome. Radiographic evaluation was d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
1
2
0
Order By: Relevance
“…Conversely, Melis et al reported that lucent lines were observed in 57% of patients at an average postoperative time of 9.6 years [20], suggesting the need for caution in the long-term course. Furthermore, spot welds in non-cemented cases appeared predominantly in the distal part of the coating of the stem in Zones 2 and 4, similar to the locations of spot welds observed after THA [23][24][25]. Bone resorption reportedly occurs around the humeral stem relatively early in the postoperative period, with most sites appearing in the proximal part of the stem [2,26,27].…”
Section: Discussionsupporting
confidence: 66%
“…Conversely, Melis et al reported that lucent lines were observed in 57% of patients at an average postoperative time of 9.6 years [20], suggesting the need for caution in the long-term course. Furthermore, spot welds in non-cemented cases appeared predominantly in the distal part of the coating of the stem in Zones 2 and 4, similar to the locations of spot welds observed after THA [23][24][25]. Bone resorption reportedly occurs around the humeral stem relatively early in the postoperative period, with most sites appearing in the proximal part of the stem [2,26,27].…”
Section: Discussionsupporting
confidence: 66%
“…It is one of the most well-known hip implants manufactured by DePuy Synthes. The SUMMIT hip implant is considered clinically effective with a revision rate of 1.78% as per a total hip replacement (THR) study on 817 patients [ 35 ]. This includes both cemented and non-cemented solutions to accommodate a broad range of patient requirements [ 35 ].…”
Section: Methodsmentioning
confidence: 99%
“…The SUMMIT hip implant is considered clinically effective with a revision rate of 1.78% as per a total hip replacement (THR) study on 817 patients [ 35 ]. This includes both cemented and non-cemented solutions to accommodate a broad range of patient requirements [ 35 ]. After assessing these values, the SUMMIT Hip System was considered for this inquiry.…”
Section: Methodsmentioning
confidence: 99%